PENGARUH PROFITABILITAS DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN - Deviana, Novia; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out the influence of profitability and investment decision to the firm value with theuse of dividend policy as the intervening variable. The population is all manufacturing companies which arelisted in Indonesia Stock Exchange (IDX) in 2011-2014 periods. The sample collection technique has been doneby using purposive sampling and 20 manufacturing companies have been selected as samples. The analysistechnique has been carried out by using path analysis method. The result of this research shows that profitabilitydoes not give any significant influence to the dividend policy. Profitability has positive to the firm value.Investment decision give positive influence to the dividend policy. Investment decision give positive influence tothe firm value. The dividend policy give negative influence to the firm value. Profitability does not give anyinfluence to the dividend policy whereas the dividend policy give negative influence to the firm value, so that thedividend policy cannot mediate the profitability to the firm value. Investment decision give positive influence tothe dividend policywhereas the dividend policy give negative influence to the firm value, so that the dividendpolicy can mediate the investment decision to the firm value.Keywords: firm value, profitability, investment decision, dividend policy